Предмет: Алгебра,
автор: Аноним
Упростите выражение:
а) 3а + 7b – 6а - 4 b
б) 8с + (5 – с) – (7 + 11с)
в) 4 – 5(3y + 8)
Ответы
Автор ответа:
0
1)(3а-6а)+(7б-4б)= -3а+3б
2)8с+5-с-7-11с=(8с-с-11с)-(7-5)= -4с-2
3)4-15у+40=(4-40)-15у= -36-15у
2)8с+5-с-7-11с=(8с-с-11с)-(7-5)= -4с-2
3)4-15у+40=(4-40)-15у= -36-15у
Похожие вопросы
Предмет: Математика,
автор: st5320805
Предмет: Биология,
автор: ajgunabbasova03
Предмет: Английский язык,
автор: Veltar
Предмет: Геометрия,
автор: alicooon
Предмет: География,
автор: Blood71